IMPLEMENTASI METODE DESIGN THINKING PADA PERANCANGAN USER EXPERIENCE APLIKASI PENANGANAN GANGGUAN KECEMASAN - Shanda, Rima (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
Anxiety disorder is one of the mental health disorders that are still a challenge in Indonesian society. College students is one of the most vulnerable populations affected by anxiety disorders. Through questionnaires distributed to UII students, it was found that anxiety often arises when they face various problems This anxiety disorder causes several symptoms for students, both physical and psychological symptoms. This makes it difficult for sufferers to carry out daily activities normally. The implementation of a healthy lifestyle is one of the ways that individuals with anxiety disorders can use to reduce the onset of anxiety symptoms. Therefore, this study aims to design an application user experience that can help overcome anxiety disorders through the application of a healthy lifestyle. This research uses a design thinking method to ensure that the application designed has functionality that is in accordance with user problems and needs. To test the user experience of the application, usability testing is carried out by measuring three aspects, namely efficiency, effectiveness, and user satisfaction. The results of this measurement show that the application has a success rate value of 90% in the aspect of effectiveness, a time-based efficiency value of 0.0834 goals / sec in the aspect of efficiency, and gets a grade scale of "A" and the category "excellent" in the aspect of user satisfaction.